(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background: Ketamine is an N-methyl-D-aspartate (NMDA) receptor blocking agent, which is used for induction and maintenance of anesthesia. It affects the cerebral cortex and has an impact on learning and memory functions; suggesting that any changes in NMDA receptors function will have an adverse outcome on learning and memory abilities. Objective: To assess the histological changes in the frontal and parietal cortices of mice offspring’s after prenatal exposure to therapeutic doses of ketamine. Methods: Thirty pregnant mice were included in this study. They were divided into two groups named experimental and control groups (15 mice for each group). Those of experimental group were injected intraperitoneally with ketamine in a dose of 50 mg/kg/day on the 5th, 10th, 15th and 20th days of gestational age to showing effect of the ketamine after injection of it in all trimesters of pregnancy, while those of the control group were injected with distal water only with the same volume. The paraffin block sections of frontal and parietal cerebral cortices of newborn mice were stained by nissl stain. Results: In the control group, the mean number of Nissl stained cells in the frontal cortex showed a statistically significant increase compared to that of parietal cortex, while statistical non-significant decrease in the mean number of nissel stained cells of frontal cortex compared to that of parietal cortex. Conclusion: Iatrogenic apoptotic changes were seen in the cerebral cortex of the experimental mice after prenatal exposure to ketamine and it is more considerable in the frontal cortex than the parietal cortex. Keywords: Frontal cortex, parietal cortex, ketamine, nissl stain, development Citation: Najm MS, Mubarak HJ, Jarullah HA. Nissl stain expression in the frontal and parietal cortices of the newborn mice after prenatal exposure to ketamine. Iraqi JMS. 2018; 16(3): 268-278. doi: 10.22578/IJMS.16.3.6